Muscial representation in Rafiq Sabir’s Poetry - Mohammed Omer Ibrahim; Hawkar Mohammed Rasheed (QALAAI ZANIST SCIENTIFIC JOURNAL, 2025)
Musical interpretation is one of the main criteria of poetic text. Yes, there is music in every poem and no details about it. Music can give poetry a new body, beauty and sophistication of words, by which hidden meanings are embodied, and thus music is created from sound and sound is the language of poetry and line Poet At present, this subject is of great interest to the audience, but the importance of music and its characteristics has attracted more attention. Conduct this search for poetic melody in Rafiq Saber’s poems, and discover the internal and external melody of his poems. Our goal is to present the musical structure in the poet’s poems and through our discussion and descriptive analytical methodology. This research consists of a summary, introduction, sections, conclusion, and list of sources in the first part. Foreign music is introduced in the poet’s poems. In the second part we introduce the internal melody of the poet’s text.